Cost-utility analysis of indacaterol in Germany: a once-daily maintenance bronchodilator for patients with COPD. - Price, D; Gray, A; Gale, R; Asukai, Y; Mungapen, L; Lloyd, A; Peters, L; Neidhardt, K; Gantner, T (2011)
INTRODUCTION: Indacaterol is a novel inhaled once-daily long-acting beta(2)-agonist (LABA) for the maintenance treatment of COPD that has been compared to existing inhaled monotherapies on a number of symptomatic endpoints in clinical studies. With constrained healthcare budgets, the objective of this analysis was to evaluate the cost-effectiveness of indacaterol 150 μg, the approved starting dose for maintenance therapy, from a German heath service perspective against the most widely used bronchodilator tiotropium, and the twice-daily LABA, salmeterol. METHODS: A Markov model was developed with the following main health states: Mild, Moderate, Severe, and Very Severe COPD, based on pre-bronchodilator FEV(1) measures reported in the indacaterol clinical trials, and death. Each disease severity health state had two associated health states for severe or non-severe exacerbation. The model considered patients with moderate to severe COPD, with a mean age of 64 years. The base case time horizon was three years, with discounting set at 3% for costs and benefits. Selected clinical inputs and health state utilities were derived from indacaterol clinical trials, while costs were based on publicly available drug prices and tariffs or published sources. Inputs describing disease progression were based on published data on the rate of FEV(1) decline. RESULTS: Point-estimates show that indacaterol 150 μg is dominant (lower total costs and better outcomes) against tiotropium and salmeterol. An alternative analysis comparing indacaterol 300 μg (maximum dose) against tiotropium, showed an incremental cost-effectiveness ratio (ICER) of approximately €28,300 per QALY. CONCLUSION: Indacaterol is cost-effective compared to tiotropium and salmeterol.